2016
DOI: 10.7863/ultra.15.01028
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Evaluation in Patients With Pulmonary Hypertension

Abstract: Real-time 3DE is a feasible, repeatable, and noninvasive method for accessing cyclic RA volume and function changes, such as those that occur with varying RV status in patients with pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
1
5
0
2
Order By: Relevance
“…Both Willens et al and Cioffi demonstrated that RA volume was larger in patients with PH (19,20). Similar results were obtained by Deng et al (21), who employed 3D echocardiography, and by Sato et al who employed cardiac MRI-based volume assessment (22). Similar to those studies, our current study, which is based upon volumetric analysis of CTPA data, shows the association between RA volume and PH.…”
Section: Discussionsupporting
confidence: 89%
“…Both Willens et al and Cioffi demonstrated that RA volume was larger in patients with PH (19,20). Similar results were obtained by Deng et al (21), who employed 3D echocardiography, and by Sato et al who employed cardiac MRI-based volume assessment (22). Similar to those studies, our current study, which is based upon volumetric analysis of CTPA data, shows the association between RA volume and PH.…”
Section: Discussionsupporting
confidence: 89%
“…13 Increased right atrial pressure and volume leads to RA structural remodeling that manifests as chamber enlargement. Furthermore, RA enlargement may often occur before RV enlargement 14 due to the consequences of increased volume. Previous studies have demonstrated that changes in cardiac chamber volume may precede pressure changes in both the ventricles and atria.…”
Section: Discussionmentioning
confidence: 99%
“…Another study illustrated that 3D echocardiography enables the measurement of RA volume and phasic function, highlighting its feasibility and consistency throughout the cardiac cycle [84]. In patients with PH, the volumetric assessment of the RA and the modifications in passive and active emptying fractions, particularly when precedes RV dilation, can become meaningful prognostic markers.…”
Section: Right Atrium Volume and Strainmentioning
confidence: 99%